Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 148565 by mathmax by abdo last updated on 29/Jul/21

calculate ∫_(−∞) ^(+∞)   ((x^2 dx)/((x^2 −x+1)(x^2  +x+1)))

calculate+x2dx(x2x+1)(x2+x+1)

Answered by Ar Brandon last updated on 29/Jul/21

Υ=∫_(−∞) ^(+∞) ((x^2 dx)/((x^2 −x+1)(x^2 +x+1)))=2∫_0 ^∞ ((x^2 dx)/((x^2 −x+1)(x^2 +x+1)))      =2∫_0 ^1 ((x^2 dx)/((x^2 −x+1)(x^2 +x+1)))+2∫_1 ^∞ ((x^2 dx)/((x^2 −x+1)(x^2 +x+1)))      =2∫_0 ^1 ((x^2 dx)/((x^2 −x+1)(x^2 +x+1)))+2∫_0 ^1 (dx/((x^2 −x+1)(x^2 +x+1)))      =2∫_0 ^1 ((x^2 +1)/((x^2 −x+1)(x^2 +x+1)))dx=2∫_0 ^1 ((x^2 +1)/(x^4 +x^2 +1))dx      =2∫_0 ^1 ((1+(1/x^2 ))/(x^2 +1+(1/x^2 )))dx=2∫_0 ^1 ((1+(1/x^2 ))/((x−(1/x))^2 +3))dx      =2∫_0 ^1 ((d(x−(1/x)))/((x−(1/x))^2 +3))=(2/( (√3)))[arctan(((x^2 −1)/( (√3)x)))]_0 ^1 =(π/( (√3)))

Υ=+x2dx(x2x+1)(x2+x+1)=20x2dx(x2x+1)(x2+x+1)=201x2dx(x2x+1)(x2+x+1)+21x2dx(x2x+1)(x2+x+1)=201x2dx(x2x+1)(x2+x+1)+201dx(x2x+1)(x2+x+1)=201x2+1(x2x+1)(x2+x+1)dx=201x2+1x4+x2+1dx=2011+1x2x2+1+1x2dx=2011+1x2(x1x)2+3dx=201d(x1x)(x1x)2+3=23[arctan(x213x)]01=π3

Answered by mathmax by abdo last updated on 29/Jul/21

Ψ=∫_(−∞) ^(+∞)  (x^2 /((x^2 −x+1)(x^2  +x+1)))dx let Λ(z)=(z^2 /((z^2 −z+1)(z^2  +z+1)))  poles of Λ?  z^2 −z+1=0→Δ=−3⇒z_1 =((1+i(√3))/2) =e^((iπ)/3)  and z_2 =((1−i(√3))/2)=e^(−((iπ)/3))   z^2 +z+1=0→Δ=−3 ⇒x_1 =((−1+i(√3))/2)=e^((2iπ)/3)  ⇒x_2 =e^(−((2iπ)/3))  ⇒  Λ(z)=(z^2 /((z−e^((iπ)/3) )(z−e^(−((iπ)/3)) )(z−e^((2iπ)/3) )(z−e^(−((2iπ)/3)) )))  ∫_(−∞) ^(+∞)  Λ(z)dz=2iπ{Res(Λ,e^((iπ)/3) )+Res(Λ,e^((2iπ)/3) )}  Res(Λ,e^((iπ)/3) ) =(e^((2iπ)/3) /(2isin((π/3))×))(((e^((iπ)/3) −1))/(e^(iπ) −1))  =(1/(−4i×((√3)/2)))(−1−e^((2iπ)/3) ) =((1+e^((2iπ)/3) )/(2i(√3)))  Res(Λ,e^((2iπ)/3) ) =(e^((4iπ)/3) /(2isin(((2π)/3))))×((e^((2iπ)/3)  +1)/2)  =((1+e^((4iπ)/3) )/(4i×((√3)/2)))=((1+e^((4iπ)/3) )/(2i(√3))) ⇒  ∫_(−∞) ^(+∞)  Λ(z)dz=((2iπ)/(2i(√3))){1+e^((2iπ)/3)  +1−e^((iπ)/3) }  =(π/( (√3))){2 −(1/2)+((i(√3))/2) −(1/2)−i((√3)/2)} =(π/( (√3))) ⇒Ψ=(π/( (√3))) .

Ψ=+x2(x2x+1)(x2+x+1)dxletΛ(z)=z2(z2z+1)(z2+z+1)polesofΛ?z2z+1=0Δ=3z1=1+i32=eiπ3andz2=1i32=eiπ3z2+z+1=0Δ=3x1=1+i32=e2iπ3x2=e2iπ3Λ(z)=z2(zeiπ3)(zeiπ3)(ze2iπ3)(ze2iπ3)+Λ(z)dz=2iπ{Res(Λ,eiπ3)+Res(Λ,e2iπ3)}Res(Λ,eiπ3)=e2iπ32isin(π3)×(eiπ31)eiπ1=14i×32(1e2iπ3)=1+e2iπ32i3Res(Λ,e2iπ3)=e4iπ32isin(2π3)×e2iπ3+12=1+e4iπ34i×32=1+e4iπ32i3+Λ(z)dz=2iπ2i3{1+e2iπ3+1eiπ3}=π3{212+i3212i32}=π3Ψ=π3.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com